Integrasi Kajian Teologis dan Peran Pastoral bagi Tenaga Kerja Indonesia dalam Menghadapi Isu LGBT di Malaysia - Lestimar Sihombing; Andreas Eko Nugroho; Jacob Mesakh (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
The phenomenon of Indonesian migrant workers (TKI) in Malaysia involves not only economic issues but also complex social and spiritual challenges. In an era of globalisation, cultural openness, and rapid digital development, migrant workers face moral and faith struggles, particularly related to LGBT issues that increasingly influence public discourse and personal values. This situation highlights the urgent need for churches and pastoral ministries to provide contextual accompaniment for diaspora communities. This study integrates theological reflection and pastoral ministry to assist TKI in responding to LGBT issues based on the love and truth of Christ. Using a qualitative literature review approach, the research examines theological, pastoral, and Christian educational psychology sources. The findings show that the integration of theology and pastoral care effectively fosters critical faith understanding, empathetic attitudes, and ethical behaviour amid value pluralism. Pastoral counselling grounded in love and incarnational theology is especially relevant in the diaspora context. This study contributes to contemporary pastoral practice and Christian educational psychology in the global era.